Beyond the Halogen Bond: Examining the Limits of Extended Polybromide Networks through Quantum‐Chemical Investigations. Issue 5 (4th February 2016) - Easton, Max E.; Chan, Bun; Masters, Anthony F.; Radom, Leo; Maschmeyer, Thomas
Abstract: The bonding environments of some polybromide monoanions and networks were examined by quantum‐chemical methods to investigate electronic interactions between dibromine–dibromine contacts. Examination of thermodynamic parameters and a bond critical point analysis give strong evidence for such bonding modes, which have been previously treated disparately in the literature. The thermodynamic stability of large polybromides up to [Br37 ] − was also predicted by these methods. Abstract : Bonding experience : Quantum‐chemical calculations demonstrate the thermodynamic stability of polybromide monoanions up to [Br37 ] − and show evidence of bonding within these networks. The results represent a significant step towards resolving the controversy surrounding the bonding nature of these materials.